(untitled) (Applied Biological Research, 2016)
Herbicides are known to affect the metabolic parameters in fishes. For this reason a study was designed to assess the effects of herbicide propanil (3’,4’- dichloropropionanilide) on common carp (Cyprinus carpio L.) through antioxidant indices and other neurotoxicological parameters. Fishes were exposed to two concentration of propanil (2 and 4 mg L-1) for 6 and 48 h and effects on neurtoxicity biomarkers [acetylcholinesterase (AChE), Na+/K+- ATPase] and oxidative stress parameters [reduced glutathione levels, superoxide dismutase, catalase, thiobarbituric acid reactive substances and protein oxidation (protein carbonyl) were studied. Study revealed that propanil exposure disturbed antioxidant status, increased lipid peroxidation and protein carbonyl levels in fishes at both doses. Activity of neurotoxicity enzymes AChE and Na+/K+-ATPase was inhibited at both the doses of propanil exposure. Propanil was more toxic at higher doses at both the lengths of exposure.